(In)distinção entre a casa e a rua: uma análise dos discursos sobre o Airbnb na/em rede - Oliveira, Rafael Ricardo de (2021)
In this work, through the Discourse Analysis approach, we take the city (ORLANDI, 1999; 2004; 2010; 2011) as an important part of the constitution of the subject and the senses, and the digital space as one of the places where these senses are formulated and circulate. For Dias (2011a; 2011b), cities have been changing according to e-, that is, the technological instruments that are part of our daily lives institute a new form of relationship between the subjects and the subjects with the urban space. Thus, thinking about the meanings of city and urban space means considering how technologies have been affecting this space and the relationships that are established in/by it. The digital space houses numerous digital platforms, which permeate the most diverse sectors, signaling for a new way of dividing material goods, work and spaces and instruments previously considered to be of the private order when organizing the subjects in networks or communities with interests common. Among them, Airbnb has mobilized millions of users who opt for this service given the practicality and economy that the company provides, since it makes it possible to rent accommodation anywhere in the world in a few clicks. Considering this relationship between urban space - subject to interpretation - and digital space, based on the materialist theory of discourse, our main objective was: to understand the city as a space for the production of meanings and the digital space as the place where speeches are formulated and circulate, producing their effects. More specifically it was: a) understand the city as a space in which the urban experience of Airbnb takes place; b) understand the digital space as the place where both Airbnb's advertising discourse and the speeches about that company materialize and produce their effects; c) check which speeches are produced and circulated on/in network about guests/hosts, in the cities where Airbnb operates. However, during our analytical gesture, other questions were present (and are important) to understand the process of producing meanings about the largest hosting application in the world such as the concepts of Smart Cities and Blockchain. After combining theory and analysis and as one of the results obtained, we conclude that Airbnb, through advertising discourse, modified meanings already crystallized, such as home and street. The sense of “living” also slips, producing, in the subject, effects of a sense of belonging. In summary, based on the use of Communication strategies and Advertising, Airbnb's discourse aims to convince the subject, based on the discourses of economy and security, that he can make dreams come true. However, it silences the negative meanings it produces in the urban space.